The Challenges of Caring for People Dying From COVID-19: A Multinational, Observational Study (CovPall) - Oluyase, Adejoke O. (J Pain Symptom Manage, 2021)
CONTEXT: Systematic data on the care of people dying with COVID-19 are scarce. OBJECTIVES: To understand the response of and challenges faced by palliative care services during the COVID-19 pandemic, and identify associated factors. METHODS: We surveyed palliative care and hospice services, contacted via relevant organizations. Multivariable logistic regression identified associations with challenges. Content analysis explored free text responses. RESULTS: A total of 458 services responded; 277 UK, 85 rest of Europe, 95 rest of the world; 81% cared for patients with suspected or confirmed COVID-19, 77% had staff with suspected or confirmed COVID-19; 48% reported shortages of Personal Protective Equipment (PPE), 40% staff shortages, 24% medicines shortages, 14% shortages of other equipment. Services provided direct care and education in symptom management and communication; 91% changed how they worked. Care often shifted to increased community and hospital care, with fewer admissions to inpatient palliative care units. Factors associated with increased odds of PPE shortages were: charity rather than public management (OR 3.07, 95% CI 1.81–5.20), inpatient palliative care unit rather than other settings (OR 2.34, 95% CI 1.46–3.75). Being outside the UK was associated with lower odds of staff shortages (OR 0.44, 95% CI 0.26–0.76). Staff described increased workload, concerns for their colleagues who were ill, whilst expending time struggling to get essential equipment and medicines, perceiving they were not a front-line service. CONCLUSION: Palliative care services were often overwhelmed, yet felt ignored in the COVID-19 response. Palliative care needs better integration with health care systems when planning and responding to future epidemics/pandemics.